In vitro micropropagation of Anthurium andraeanum through thin cell layer culture - Lan, Trần Thị Ngọc; Anh, Trần Thị Hoàn (Vietnam Journal of Biotechnology, 2018)
Anthurium is a kind of major cut flower species and economically important genera in the family Araceae. A regeneration system of Anthurium andreanum from callus culture is studied along with improving propagation process. Optimal medium for callus formation from the longitudinal thin cell layer leaf culture was ½ MS (Murashige, Skoog, 1962) supplemented with 30 g/l sucrose, 1 g/l casein hydrolysate (CH), 8 g/l agar, 1.5 mg/1 BA and 0.2 mg/1 2,4-D (the induction callus rate of 77.33%). Calli multiplied with 21.45-fold fresh mass increase when they were subcultured once 60 days on the ½ MS supplemented with 1 g/l CH, 30 g/l sucrose, 1,5 mg/l BA and 8 g/l agar. The highest ratio of shoot induced from callus culture was also on this medium (18.54 shoots per explants). The medium ½ MS supplemented with 20 g/l sucrose, 1 g/l AC, 8 g/l agar and without plant growth regulators is the most suitable one for root formation of these multiple-shoots. The highest survival rate is observed with substrate mixture of fern moss and rice husk ash in the ratio of 1:1 (gave the best regeneration rate of 100% in the ex vitro culture) and no morphological variations were observed in these plantlets after about thirty days,acclimatized in the greenhouse. Histological observation showed that these calli contained embryogenic cells with their fast growth.It could be an alternative tool for propagation and preservation of Anthurium andreanum, a valuable cultivar